Analysis of the bacterial flora of venous leg ulcers in patients hospitalized in the Department of Dermatology in Kielce Hospital during 2006-2010 - Cyran-Stemplewska, Sylwia; Kłujszo, Elżbieta; Sodo, Anna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Patients with leg ulcers constitute a large proportion of persons hospitalized in the Department of Dermatology in Kielce. Leg ulcers affect 1-2% of the European population. Objective . To analyse the distribution of pathogens isolated from leg ulcers of patients hospitalized during 2006-2010. Material and methods . The analysis included 200 bacteriological cultures taken from the ulcers at the time of patient’s admission to the department. For statistical analysis Student’s t test was used. All pathogens were divided into six groups. Distribution of the most common pathogens, distribution of the bacteria divided into groups during 2006-2010 and the character of pathogens depending on the duration of the ulceration and diabetes mellitus have been analysed. Results . The analysis revealed Staphylococcus aureus (48%) to be the predominant cultured pathogen followed by Pseudomonas aeruginosa (26.5%), Enterococcus faecalis (22%), Proteus mirabilis (14%) and Escherichia coli (14%). In the investigated period the decrease of Staphylococcus aureus isolates and the increase of isolates of Enterococcus faecalis and Pseudomonas aeruginosa has been observed. The study demonstrated more frequent presence of Proteus mirabilis and Pseudomonas aeruginosa in patients with diabetes mellitus and Gram negative bacteria in ulcers lasting more than 5 years. Conclusions . Knowledge of the changes in the distribution of bacterial flora of leg ulcers during 2006-2010 determines the decision on their treatment, especially with antibiotics.